For part (a) the answer is 400 grams for part (b) 198.63 grams and for part (c) 20 years.
<h3>What is exponential decay?</h3>
During exponential decay, a quantity falls slowly at first before rapidly decreasing. The exponential decay formula is used to calculate population decline and can also be used to calculate half-life.
We have an equation for radioactive decay:
![\rm m(t) = 400e^{-0.035t}](https://tex.z-dn.net/?f=%5Crm%20m%28t%29%20%3D%20400e%5E%7B-0.035t%7D)
a) Plug t = 0
![\rm m(0) = 400e^{-0.035\times 0}](https://tex.z-dn.net/?f=%5Crm%20m%280%29%20%3D%20400e%5E%7B-0.035%5Ctimes%200%7D)
m(0) = 400 grams
b) plug t = 20 years
![\rm m(20) = 400e^{-0.035\times 20}](https://tex.z-dn.net/?f=%5Crm%20m%2820%29%20%3D%20400e%5E%7B-0.035%5Ctimes%2020%7D)
After solving:
m(20) = 198.63 grams
c) Plug m(t) = m(0)/2 = 400/2 = 200 grams
![\rm 200 = 400e^{-0.035t}](https://tex.z-dn.net/?f=%5Crm%20200%20%3D%20400e%5E%7B-0.035t%7D)
x = 19.80 years ≈ 20 years
Thus, for part (a) the answer is 400 grams for part (b) 198.63 grams and for part (c) 20 years.
Learn more about the exponential decay here:
brainly.com/question/14355665
#SPJ1
Answer:
6 x 2.5 = 15
8 x 2.5 = 20
L x W = 300 square units
Step-by-step explanation:
Brainliest?
Well what is the problem ?
Answer:
See Below.
Step-by-step explanation:
We have the equation:
![\displaystyle y = \left(3e^{2x}-4x+1\right)^{{}^1\! / \! {}_2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20y%20%3D%20%5Cleft%283e%5E%7B2x%7D-4x%2B1%5Cright%29%5E%7B%7B%7D%5E1%5C%21%20%2F%20%5C%21%20%7B%7D_2%7D)
And we want to show that:
![\displaystyle y \frac{d^2y }{dx^2} + \left(\frac{dy}{dx}\right) ^2 = 6e^{2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%5Cfrac%7Bd%5E2y%20%7D%7Bdx%5E2%7D%20%2B%20%5Cleft%28%5Cfrac%7Bdy%7D%7Bdx%7D%5Cright%29%20%5E2%20%3D%206e%5E%7B2x%7D)
Instead of differentiating directly, we can first square both sides:
![\displaystyle y^2 = 3e^{2x} -4x + 1](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%5E2%20%3D%203e%5E%7B2x%7D%20-4x%20%2B%201)
We can find the first derivative through implicit differentiation:
![\displaystyle 2y \frac{dy}{dx} = 6e^{2x} -4](https://tex.z-dn.net/?f=%5Cdisplaystyle%202y%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%206e%5E%7B2x%7D%20-4)
Hence:
![\displaystyle \frac{dy}{dx} = \frac{3e^{2x} -2}{y}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B3e%5E%7B2x%7D%20-2%7D%7By%7D)
And we can find the second derivative by using the quotient rule:
![\displaystyle \begin{aligned}\frac{d^2y}{dx^2} & = \frac{(3e^{2x}-2)'(y)-(3e^{2x}-2)(y)'}{(y)^2}\\ \\ &= \frac{6ye^{2x}-\left(3e^{2x}-2\right)\left(\dfrac{dy}{dx}\right)}{y^2} \\ \\ &=\frac{6ye^{2x} -\left(3e^{2x} -2\right)\left(\dfrac{3e^{2x}-2}{y}\right)}{y^2}\\ \\ &=\frac{6y^2e^{2x}-\left(3e^{2x}-2\right)^2}{y^3}\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Cfrac%7Bd%5E2y%7D%7Bdx%5E2%7D%20%26%20%3D%20%5Cfrac%7B%283e%5E%7B2x%7D-2%29%27%28y%29-%283e%5E%7B2x%7D-2%29%28y%29%27%7D%7B%28y%29%5E2%7D%5C%5C%20%5C%5C%20%26%3D%20%5Cfrac%7B6ye%5E%7B2x%7D-%5Cleft%283e%5E%7B2x%7D-2%5Cright%29%5Cleft%28%5Cdfrac%7Bdy%7D%7Bdx%7D%5Cright%29%7D%7By%5E2%7D%20%5C%5C%20%5C%5C%20%26%3D%5Cfrac%7B6ye%5E%7B2x%7D%20-%5Cleft%283e%5E%7B2x%7D%20-2%5Cright%29%5Cleft%28%5Cdfrac%7B3e%5E%7B2x%7D-2%7D%7By%7D%5Cright%29%7D%7By%5E2%7D%5C%5C%20%5C%5C%20%26%3D%5Cfrac%7B6y%5E2e%5E%7B2x%7D-%5Cleft%283e%5E%7B2x%7D-2%5Cright%29%5E2%7D%7By%5E3%7D%5Cend%7Baligned%7D)
Substitute:
![\displaystyle y\left(\frac{6y^2e^{2x}-\left(3e^{2x}-2\right)^2}{y^3}\right) + \left(\frac{3e^{2x}-2}{y}\right)^2 =6e^{2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%5Cleft%28%5Cfrac%7B6y%5E2e%5E%7B2x%7D-%5Cleft%283e%5E%7B2x%7D-2%5Cright%29%5E2%7D%7By%5E3%7D%5Cright%29%20%2B%20%5Cleft%28%5Cfrac%7B3e%5E%7B2x%7D-2%7D%7By%7D%5Cright%29%5E2%20%3D6e%5E%7B2x%7D)
Simplify:
![\displaystyle \frac{6y^2e^{2x}- \left(3e^{2x} -2\right)^2}{y^2} + \frac{\left(3e^{2x}-2\right)^2}{y^2}= 6e^{2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B6y%5E2e%5E%7B2x%7D-%20%5Cleft%283e%5E%7B2x%7D%20-2%5Cright%29%5E2%7D%7By%5E2%7D%20%2B%20%5Cfrac%7B%5Cleft%283e%5E%7B2x%7D-2%5Cright%29%5E2%7D%7By%5E2%7D%3D%206e%5E%7B2x%7D)
Combine fractions:
![\displaystyle \frac{\left(6y^2e^{2x}-\left(3e^{2x} - 2\right)^2\right) +\left(\left(3e^{2x}-2\right)^2\right)}{y^2} = 6e^{2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B%5Cleft%286y%5E2e%5E%7B2x%7D-%5Cleft%283e%5E%7B2x%7D%20-%202%5Cright%29%5E2%5Cright%29%20%2B%5Cleft%28%5Cleft%283e%5E%7B2x%7D-2%5Cright%29%5E2%5Cright%29%7D%7By%5E2%7D%20%3D%206e%5E%7B2x%7D)
Simplify:
![\displaystyle \frac{6y^2e^{2x}}{y^2} = 6e^{2x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B6y%5E2e%5E%7B2x%7D%7D%7By%5E2%7D%20%3D%206e%5E%7B2x%7D)
Simplify:
![6e^{2x} \stackrel{\checkmark}{=} 6e^{2x}](https://tex.z-dn.net/?f=6e%5E%7B2x%7D%20%5Cstackrel%7B%5Ccheckmark%7D%7B%3D%7D%206e%5E%7B2x%7D)
Q.E.D.
Answer:
Approximately 2.83
Step-by-step explanation: